2002
DOI: 10.1051/lait:2002030
|View full text |Cite
|
Sign up to set email alerts
|

Article

Abstract: -High-fat and skim-milk powders were produced under constant processing conditions from Spring and Autumn herd milks. The influence of the seasonal variation in protein and solid-fat contents at 10 o C of these milks on some properties of the milk powders was determined. The free-fat content and the median particle size of high-fat milk powders were significantly (P < 0.05) affected by the protein content and solid-fat content of the milk. There was a curvilinear relationship between the median powder particle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…According to Afoakwa et al (2007), the observed differences may be related to formulation, manufacturing techniques, tempering, polymorphism (stability of fats) and cooling temperature controls, impacting on the final texture (hardness) of chocolate. Keogh et al (2002) concluded that hardness is a good indicator of good tempering, or degree to which a stable fat network has been formed.…”
Section: Chemical Compositionmentioning
confidence: 99%
“…According to Afoakwa et al (2007), the observed differences may be related to formulation, manufacturing techniques, tempering, polymorphism (stability of fats) and cooling temperature controls, impacting on the final texture (hardness) of chocolate. Keogh et al (2002) concluded that hardness is a good indicator of good tempering, or degree to which a stable fat network has been formed.…”
Section: Chemical Compositionmentioning
confidence: 99%
“…Similarly, [20] also observed that the use of gelatin at 0.2-0.3 percent levels improves the quality of yoghurt with reduced syneresis. This might be due to effective immobilization of the aqueous phase by the gelatin in the yoghurt network which thus significantly reduced the susceptibility to syneresis [21,22]. It is worth noting that large amounts of gelatin would induce the formation of a gel network with the sodium caseinate in the yogurt mixture [23].…”
Section: Discussionmentioning
confidence: 99%